1996
DOI: 10.1002/(sici)1096-9071(199612)50:4<342::aid-jmv10>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Detection and typing of molluscum contagiosum virus in skin lesions by using a simple lysis method and polymerase chain reaction

Abstract: A polymerase chain reaction (PCR) assay for the rapid detection and typing of molluscum contagiosum virus (MCV) was developed. The target DNA was a 393 base pair (bp) segment, which is present in the coding region of the MCV p43K gene product. Release of MCV DNA from skin lesions was performed by using a simple procedure that provided suitable template DNA for amplification, and allowed detection of MCV directly in clinical material. The PCR yielded a unique 393 bp product when MCV DNA was used as template. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…The use of PCR to identify MCV infection (Nunez et al, 1996;Thompson, 1997) and the use of restriction mapping or hybridization to characterize the subtypes (Darai et al, 1986;Porter et al, 1987;Thompson, 1997) has been previously reported. Although these are functional assays, they are not without their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PCR to identify MCV infection (Nunez et al, 1996;Thompson, 1997) and the use of restriction mapping or hybridization to characterize the subtypes (Darai et al, 1986;Porter et al, 1987;Thompson, 1997) has been previously reported. Although these are functional assays, they are not without their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PCR assays were established that amplified OPV with species-specific amplicon lengths [70]. Some notable conventional PCR assays have been published for other human poxviruses [43,[71][72][73][74][75]]. …”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…The diagnosis may also be confirmed by electron microscopy (6) and PCR (16,18). Laboratory testing is most often conducted on lesions from the moist genital area, where MCV infections/symptoms may be atypical and difficult to differentiate from those of HSV (8,11).…”
Section: Case Reportmentioning
confidence: 99%